Decay control of cold stored Citrus clementina Hort. ex Tan. fruit by pre- and postharvest application of potassium phosphite - Maria Concetta Strano (Advances in Horticultural Science, 2015)
The effectiveness of pre- and postharvest application of potassium phosphite against naturally occuring postharvest decay and storage disorders on clementine Monreal fruit (Citrus clementina Hort. ex Tan.) was investigated. Phosphite solutions were applied according to the following experimental protocol: by spraying fruit on the trees (2.5 g/L), at fruit colour breaking and 15 days before harvest; by the combination of preharvest (2.5 g/L) and postharvest dipping application (4 g of a.i./L). Preharvest applications were compared to Phosethyl-Al solution (2.5 g/L) and water control. Decay and disorders were assessed after 30 days of cold storage at 6±1°C and 90-95% RH, followed by 7 days of shelf life at 20±2°C. The combination of pre- and postharvest application of phosphite was more effective in reducing green (Penicillium digitatum Sacc.) and blue mould (P. italicum Weh.) incidence, as compared to water control, but it was not so effective in reducing the incidence of minor decay. Potassium phosphite treatments, before harvest and in pre-postharvest combination, significantly reduced chilling injury and aging with respect to water control. Based on these results, pre and postharvest application of potassium phosphite can be considered a useful strategy to be included in an integrated approach for controlling green and blue mould of citrus fruit in storage.